Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction